Role and Responsibilities of Notary Statement on General Meeting of Shareholders (AGM) - Yuli Tri Yana; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study was to determine: 1) The powers and responsibilities of Notaries in deed statement of decision general meeting of shareholders of a limited liability company, 2) The legal consequences of a deed statement of decision general meeting of shareholders of a limited liability company, 3) Legal protection for Notaries in the making deed of declaration decision general meeting of shareholders limited liability company. The approach used in this paper is normative, with the help of primary data in the form of legal material which is two primary legal materials and secondary legal materials as the main data. The data collection was obtained by interview and literature. The data were analyzed qualitatively normative. The research results are: 1). Role of Notary in the manufacture of the Deed of General Meeting of Shareholders of the Company Limited by Act No. 30 of 2004 concerning Notary, particularly Article 15 which essentially gives some authority to the Notary as a public official in performing their duties, namely: Notary authorized to make an authentic deed regarding all deeds, agreements, and provisions required by legislation and / or desired by the stakeholders to be stated in an authentic deed, deed of guarantee certainty of the date of manufacture, save deed, giving grosse, copy, and official copies, all of it along the manufacture the deed was not also be assigned or excluded to other officials or any other person specified by law. 2). General Meeting of Shareholders. 3). Deed of the General Meeting of shareholders is an authentic act that is Partij Akten that deed made by the parties before a notary.